Solar activation of TiO2 intensified with graphene for degradation of Bisphenol-A in water. (1st November 2018) - Monteagudo, J.M.; Durán, A.; Chatzisymeon, E.; San Martín, I.; Naranjo, S.
Graphical abstract: Highlights: We have studied the solar degradation of BPA using TiO2 and TiO2 /graphene. TiO2 modified with 2%wt graphene improved the photocatalytic efficiency. Superoxide radical was the main oxidant species in both processes. In optimal conditions, 84% TOC removal was achieved in 120 min. HO plays a less significant role than 1 O2 in the solar/TiO2 process. Abstract: Photocatalytic degradation of a Bisphenol-A (BPA) aqueous solution was achieved using titanium dioxide (TiO2 ) and graphene-based TiO2 photocatalysts activated by solar light. First, a comparative study of the adsorption kinetics of BPA, in the presence of both catalysts, as a function of pH was performed. Then, the effect of the initial BPA concentration and catalyst loading was assessed and the optimal conditions for BPA degradation by means of heterogeneous solar photocatalysis were determined. It was observed that TiO2 modified with 2 wt% graphene improved the photocatalytic efficiency in terms of BPA mineralization. The TiO2 /graphene photocatalytic composite achieved a 16% increase in the photocatalytic mineralization of the BPA solution under solar light compared to un-doped TiO2 . This enhancement of photocatalytic efficiency is a result of the increase of active sites for BPA adsorption, the more efficient harvesting of solar light, and the inhibition of electron-hole recombination. The dynamic behavior of hydroxyl radicals and dissolved oxygen in these systems was also discussed. Finally, the roles played by hydroxyl radical, HO, superoxide radical anion, O2 −, and singlet molecular oxygen, 1 O2, were studied in both TiO2 and TiO2 /graphene systems. It was found that O2 − were the main oxidative species in both systems.